2018
DOI: 10.1080/14786419.2018.1503263
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and antifungal properties of crude extracts and isolated compounds from Lychnophora markgravii

Abstract: Antimicrobial activity of dichloromethane and ethanol extracts and five compounds: pinostrobin (I), pinocembrin (II), tectochrysin (III), galangin 3-methyl ether (IV) and tiliroside (V) isolated from Lychnophora markgravii aerial parts against fifteen microorganisms was determined. The structures of these compounds were elucidated based on ESI-MS and NMR spectroscopic data. Both extracts showed antimicrobial activity against several tested microorganisms. Pinostrobin, tectochrysin and galangin 3methyl ether sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…The study conducted by Veloz et al on Chilean propolis found that antibacterial activity of both of these compounds against Streptococcus mutans is higher than activity of polyphenols mixture or even chlorhexidine (MICs = 1.6 µg/mL), with minimum inhibitory concentrations (MICs) 1.4 µg/mL and 1.3 µg/mL, respectively [41]. Several studies have demonstrated the antibacterial activity of isolated pinocembrin against S. mutans , S. sobrinus , S. aureus , E. faecalis , L. monocytogenes , Pseudomonas aeruginosa and K. pneumoniae [42,43,44,45]. Isolated apigenin acts against Gram-negative bacteria: P. aeruginosa , K. pneumoniae , Salmonella enterica serotype Typhimurium, Proteus mirabilis and Enterobacter aerogenes [46].…”
Section: Antimicrobial Properties Of Propolismentioning
confidence: 99%
“…The study conducted by Veloz et al on Chilean propolis found that antibacterial activity of both of these compounds against Streptococcus mutans is higher than activity of polyphenols mixture or even chlorhexidine (MICs = 1.6 µg/mL), with minimum inhibitory concentrations (MICs) 1.4 µg/mL and 1.3 µg/mL, respectively [41]. Several studies have demonstrated the antibacterial activity of isolated pinocembrin against S. mutans , S. sobrinus , S. aureus , E. faecalis , L. monocytogenes , Pseudomonas aeruginosa and K. pneumoniae [42,43,44,45]. Isolated apigenin acts against Gram-negative bacteria: P. aeruginosa , K. pneumoniae , Salmonella enterica serotype Typhimurium, Proteus mirabilis and Enterobacter aerogenes [46].…”
Section: Antimicrobial Properties Of Propolismentioning
confidence: 99%
“…In fact, an ethanolic extract of propolis known as kaempferide, is used in the treatment of S. aureus skin infections. Also, kaempferide was highly effective against Enterococcus Faecalis , Listeria monocytogenes and Staphylococcus Saprophyticus ( Hernández Tasco et al, 2018 , Kharsany et al, 2019 ). Quercetin, yet another flavonoid, found in propolis, binds to the subunit of E. coli DNA gyrase to hinder bacterial activity ( Plaper et al 2003 ).…”
Section: Anti-bacterial Efficacy Of Propolismentioning
confidence: 99%
“…It is found more abundantly in roots than other secondary metabolites, such as pinocembrin and pinosylvin (Wang et al, 2016). Pinostrobin is known to have various pharmacological activities (Patel et al, 2016), including antiulcer, anti-Helicobacter pylori (Bhamarapravati et al, 2006), antioxidant, antiinflammatory, anticancer (Jaudan et al, 2018;Jones and Gehler, 2020;Sopanaporn et al, 2020), antidiarrheal, antiviral (Wu et al, 2011), antimicrobial (Hernández Tasco et al, 2020), anti-Alzheimer's, antiprotozoal, antinociceptive (Déciga-Campos et al, 2017), antimutagenic, antiplatelet (Zhang et al, 2017), antiproliferative (Siekmann et al, 2013;Jadaun et al, 2017), antileukemic (Smolarz et al, 2005), antiosteoporotic (Gu et al, 2017), and antiparasitic properties (Vechi et al, 2020). Moreover, pinostrobin can protect the gastric mucosa by reducing the ulcer area and mucosal content and reducing or eliminating submucosal edema and leukocyte infiltration.…”
Section: Introductionmentioning
confidence: 99%